2021
DOI: 10.1016/j.ajic.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trained observers (dofficers) and audits during a facility-wide COVID-19 outbreak: A mixed-methods quality improvement analysis

Abstract: Background: In response to a facility-wide COVID-19 outbreak, our tertiary acute care hospital implemented an evidence-based bundle of infection control practices including the use of audits and trained observers "dofficers" to provide real-time constructive feedback. Methods: We trained furloughed staff to perform the role of dofficer. They offered support and corrective feedback on proper PPE use and completed 21-point audits during a 4-week intervention period. Audits tracked appropriate signage, placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Our survey demonstrates that staff have taken it upon themselves to point out lapses in masking and have grown fatigued. Masking champions or “dofficers” 7 may be able to lift this burden from staff and provide regular and accurate feedback. Healthcare leadership may consider looking at models for hand hygiene and other infection control practices at their institution to draw inspiration for increasing mask compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey demonstrates that staff have taken it upon themselves to point out lapses in masking and have grown fatigued. Masking champions or “dofficers” 7 may be able to lift this burden from staff and provide regular and accurate feedback. Healthcare leadership may consider looking at models for hand hygiene and other infection control practices at their institution to draw inspiration for increasing mask compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Zehejiang, China 6 showed 73.8% correct mask use, defined as a surgical mask “worn correctly” per their Infection Prevention Department. Incorrect mask use in this study was described as “pulled downwards.” Another study from Canada 7 conducted after a facility-wide outbreak of COVID-19, showed that having an observer, or “dofficer,” monitor PPE compliance and provide intervention resulted in a reduction of errors in donning and doffing from 9.81% to 2.88%.…”
Section: Introductionmentioning
confidence: 99%
“…However, we were able to demonstrate that the implementation of PPE coaches and auditors decreased errors related to PPE by an average of 7%, with a 23% decrease in observed PPE doffing errors. 51 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 , 8 Therefore, it is recommended that PPE monitors be used to promote their colleagues’ safety by guiding them through the donning and doffing processes. 6 , 9 , 10 Early in 2020, the University of North Carolina Medical Center (UNC-MC) chose to incorporate PPE monitors as part of its comprehensive prevention strategy to reduce the risk of staff self-contamination with COVID-19. This paper describes the implementation and use of PPE monitors to observe staff donning and doffing PPE in areas treating known or suspected COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6,7,8 Therefore, it is recommended that PPE monitors be used to promote their colleagues' safety by guiding them through the donning and doffing processes. 6,9,10 period, there were only two possible healthcare-associated COVID-19 transmissions on the containment units. These transmissions were determined "possible" as there were no identified PPE breaches or community sources for exposure.…”
mentioning
confidence: 99%